Open business models : how to thrive in the new innovation landscape - Chesbrough, Henry William. (Harvard Business School Press, 2006)
'Open Business Models' introduces a framework called the 'six stages of business model development' and provides diagnostic questions for companies to assess where they are. This framework will help companies articulate what their business model is and show how they can advance along the six-stage continuum.